1998
DOI: 10.1128/jb.180.5.1287-1295.1998
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the α-Glucosidase Gene (malA) from the Hyperthermophilic ArchaeonSulfolobus solfataricus

Abstract: Acidic hot springs are colonized by a diversity of hyperthermophilic organisms requiring extremes of temperature and pH for growth. To clarify how carbohydrates are consumed in such locations, the structural gene (malA) encoding the major soluble α-glucosidase (maltase) and flanking sequences fromSulfolobus solfataricus were cloned and characterized. This is the first report of an α-glucosidase gene from the archaeal domain. malA is 2,083 bp and encodes a protein of 693 amino acids with a calculated mass of 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 54 publications
2
34
0
2
Order By: Relevance
“…7C). The malA gene (contig 025 ORF 031 in the S. solfataricus P2 database) and adjacent regions have been characterized by Rolfsmeier et al (1998). Interestingly, a 2.4 kb transcript upstream of malA, termed ORF1, was found to be transcribed upon growth on maltose.…”
Section: Discussionmentioning
confidence: 99%
“…7C). The malA gene (contig 025 ORF 031 in the S. solfataricus P2 database) and adjacent regions have been characterized by Rolfsmeier et al (1998). Interestingly, a 2.4 kb transcript upstream of malA, termed ORF1, was found to be transcribed upon growth on maltose.…”
Section: Discussionmentioning
confidence: 99%
“…This en-zyme was purified from the thermoacidophilic archeon Sulfolobus solfataricus and it is the only one that has been cloned together with the ␣-glucosidase purified from S. solfataricus 98/2 (Sunna et al, 1997;Rolfmaier and Blum, 1995). Enzymes that hydrolyze glycosidic bonds play a very important role in the biodegradation of natural polysaccharides (Di Lernia et al, 1998;Rolfmaier et al, 1998), and the extreme thermostability of SsGA was especially interesting for biotechnological applications in the glucose syrup production industry (Godfrey and West, 1996). In fact, this is a saccharifying enzyme and its optimal reaction conditions are very similar to operational parameters typically used in proximate steps of the starch process industry.…”
Section: Introductionmentioning
confidence: 99%
“…The N‐terminal protein sequences obtained from B. licheniformis KIBGE‐IB3 and B. licheniformis KIBGE‐IB3M67 were NH 2 ‐Ser‐Ser‐Asn‐Lys‐Leu‐Thr‐Thr‐Ser‐Trp‐Gly and NH 2 ‐Met‐Asp‐Asn‐Lys‐Leu‐Thr‐Thr‐Ser‐Trp‐Gly, respectively. N‐Terminal sequences of both enzymes showed no strong homology with previously characterized glucoamylases ( Table ) . It was also observed that the first two amino acid residues from the N‐Terminal end of KIBGE‐IB3 were different from that of the KIBGE‐IB3M67.…”
Section: Resultsmentioning
confidence: 85%